2014
DOI: 10.1371/journal.pone.0106278
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1 Chemokine Signalling Modulates the Apoptotic Responses to Iron Deprivation of Clathrin-Depleted DT40 Cells

Abstract: We have previously deleted both endogenous copies of the clathrin heavy-chain gene in the chicken pre B-cell-line DT40 and replaced them with clathrin under the control of a tetracycline-regulatable promoter (Tet-Off). The originally derived cell-line DKO-S underwent apoptosis when clathrin expression was repressed. We have also described a cell-line DKO-R derived from DKO-S cells that was less sensitive to clathrin-depletion. Here we show that the restriction of transferrin uptake, resulting in iron deprivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Furthermore, both DAPI staining and caspase 3/7 activity assays demonstrated that CAF conditioned medium remarkably represses HCC apoptosis. SDF-1 has been found to exert an inhibitory function on cancer apoptosis by binding with its primary receptor CXCR4, which is a seven transmembrane G-protein coupled receptor [ 25 27 ]. ELISA assays revealed that there was a dramatically higher level of soluble SDF-1 in CAF-conditioned medium than in LF-conditioned medium.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both DAPI staining and caspase 3/7 activity assays demonstrated that CAF conditioned medium remarkably represses HCC apoptosis. SDF-1 has been found to exert an inhibitory function on cancer apoptosis by binding with its primary receptor CXCR4, which is a seven transmembrane G-protein coupled receptor [ 25 27 ]. ELISA assays revealed that there was a dramatically higher level of soluble SDF-1 in CAF-conditioned medium than in LF-conditioned medium.…”
Section: Discussionmentioning
confidence: 99%